A time for war the United States and Vietnam, 1941-1975 - Schulzinger, Robert D.frey50 (New York Oxford University Press, 1997)
In A Time for War, Schulzinger paints a vast yet intricate canvas of more than three decades of conflict in Vietnam, from the first rumblings of rebellion against the French colonialists to the American intervention and eventual withdrawal. His comprehensive narrative incorporates every aspect of the warfrom the military (as seen in his brisk account of the French failure at Dienbienphu) to the economic (such as the wage increase sparked by the draft in the United States) to the political. Drawing on massive research, he offers a vivid and insightful portrait of the changes in Vietnamese politics and society, from the rise of Ho Chi Minh, to the division of the country, to the struggles between South Vietnamese president Diem and heavily armed religious sects, to the infighting and corruption that plagued Saigon. Schulzinger reveals precisely how outside powers - first the French, then the Americans - committed themselves to war in Indochina, even against their own better judgment. Roosevelt, for example, derided the French efforts to reassert their colonial control after World War II, yet Truman, Eisenhower, and their advisers gradually came to believe that Vietnam was central to American interests. The author's account of Johnson is particularly telling and tragic, describing how the president would voice clear-headed, even prescient warnings about the dangers of intervention - then change his mind, committing America's prestige and military might to supporting a corrupt, unpopular regime. Schlzinger offers sharp criticism of the American military effort, and provides a fascinating look inside the Nixon White House, showing how the Republican president dragged out the war long past the point when he realized that the United States could not win. Finally, Schulzinger paints a brilliant political and social portrait of the times, illuminating the impact of the war on the lives of ordinary Americans and Vietnamese. Schulzinger shows what the war was like for a common soldier, an American nurse, a navy flyer, a conscript in the Army of the Republic of Vietnam, a Vietcong fighter, or an antiwar protester.
Long time passing: the Vietnamese, the French, and the Americans to 1946 -- The Vietminh, the French, and the Americans: 1946-1950 -- "The fatal weakness": May 1950-April 1954 -- "Good intentions, a clear conscience, and to hell with everybody": May 1954-December 1960 -- From support to intervention: 1961-1963 -- To the brink--and beyond: 1963-1964 -- Days of reckoning: August 1964-July 1965 -- Fighting the war: 1965-1967 -- Bringing the war home: 1964-1967 -- Crack-up: 1967-1968 -- Richard Nixon's war: 1969-1973 -- The bitter end: 1973-1975.
Includes bibliography references and Index
Keywords: Indochinese War -- 1946-1954.; Vietnam War -- Foreign relations -- 1961-1975.; United States -- Vietnam -- Foreign relations; Veitnamese Conflict -- 1961-1975; Guerre d'Indochine (1946-1954).; International relations